2010 2nd International Conference on E-Business and Information System Security 2010
DOI: 10.1109/ebiss.2010.5473583
|View full text |Cite
|
Sign up to set email alerts
|

A High Capacity Information Hiding Algorithm in Color Image

Abstract: One of the important objectives of information hiding research is that secret information is embed as much as possible without the perception of the carrier is affected. A hiding information algorithm of adaptive multiple plane-bit based on space domain in color image is proposed, which has low computing complexity and high capacity of information hiding. The main idea of this algorithm is to judge each pixel at first, then embed hidden information in the designated point behind the highest non-zero bit until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…This provides very good security, but the capacity of secret data storage is less. In order to overcome the drawback of low capacity,XIE Qing et al, [2] proposed a system where information is hidden in all RGB planes based on HVS (Human Visual System). This degrades the quality of the stego image.…”
Section: Literature Surveymentioning
confidence: 99%
“…This provides very good security, but the capacity of secret data storage is less. In order to overcome the drawback of low capacity,XIE Qing et al, [2] proposed a system where information is hidden in all RGB planes based on HVS (Human Visual System). This degrades the quality of the stego image.…”
Section: Literature Surveymentioning
confidence: 99%
“…The information is encoded in a red, green, blue, and so on pattern. Xie et al [14] suggested a new technique based on the human visual system (HVS), in which critical data is encoded in all levels of RGB color space of an image. For image steganography, Gupta et al [15] provides an upgraded LSB technique.…”
Section: Related Studymentioning
confidence: 99%
“…This provides very good security. XIE Qing et al, [6] proposed a method in which the information is hidden in all RGB planes based on HVS (Human Visual System). This degrades the quality of the stego image.…”
Section: Related Workmentioning
confidence: 99%